2018
DOI: 10.3389/fneur.2018.00905
|View full text |Cite
|
Sign up to set email alerts
|

Effects of High-intensity Robot-assisted Hand Training on Upper Limb Recovery and Muscle Activity in Individuals With Multiple Sclerosis: A Randomized, Controlled, Single-Blinded Trial

Abstract: Background : Integration of robotics and upper limb rehabilitation in people with multiple sclerosis (PwMS) has rarely been investigated.Objective: To compare the effects of robot-assisted hand training against non-robotic hand training on upper limb activity in PwMS. To compare the training effects on hand dexterity, muscle activity, and upper limb dysfunction as measured with the International Classification of Functioning.Methods: This single-blind, randomized, controlled trial involved 44 PwMS (Expanded Di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
59
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(60 citation statements)
references
References 37 publications
0
59
0
1
Order By: Relevance
“…Accordingly, previous work by Pellegrino et al (16) concluded that both kinematic and electromyographic parameters might represent biomarkers that help clinicians in differentiating patients with different levels of UL motor impairment from healthy subjects (16). Surface EMG was reported to help investigate motor dysfunction as force control and fatigue in PwMS (17,18). Results are strengthened by the sEMG protocol used during a task of reaching while grasping an object.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Accordingly, previous work by Pellegrino et al (16) concluded that both kinematic and electromyographic parameters might represent biomarkers that help clinicians in differentiating patients with different levels of UL motor impairment from healthy subjects (16). Surface EMG was reported to help investigate motor dysfunction as force control and fatigue in PwMS (17,18). Results are strengthened by the sEMG protocol used during a task of reaching while grasping an object.…”
Section: Discussionmentioning
confidence: 99%
“…In this observational cross-sectional study, we used data provided by a database created for a randomized controlled trial on hand dexterity robot-assisted rehabilitation by Gandolfi et al (18) (20); Modified Ashworth Scale score evaluated at the elbow, wrist, and fingers ≤2 (21); and NHPT score between 30 and 300 s (13). Exclusion criteria were the absence of relapses or relapse-related treatments in the 3 months before the study, and other neurological or orthopedic diseases interfering with UL function.…”
Section: Methodsmentioning
confidence: 99%
“…Current evidence suggests that rehabilitation can contribute to improving UL motor function in people with MS (Gandolfi et al, 2018;Gervasoni et al, 2019) however this evidence is limited due to UL rehabilitation interventions being historically understudied, despite the impact of UL impairment in people with MS (Kraft et al, 2014). One promising yet relatively new strategy of motor rehabilitation research is the use of Virtual Reality (VR).…”
Section: Introductionmentioning
confidence: 99%
“…Some studies tested the effects of arm robotics in MS population, 3339 reporting positive effects on reaching spatio-temporal parameters and smoothness 33,40 or arm function 35,37 and hand muscle activity. 39 Furthermore, the additional use of functional electrical stimulation (FES) could improve motor learning by focusing on arm movement accuracy. 36 In conclusion, arm robotics, eventually combined with virtual reality or FES systems, is an option to deliver arm massed practice.…”
Section: Upper-extremity Robotics and Electromechanical Devicesmentioning
confidence: 99%